O TERCEIRO SETOR E A EXECUÇÃO DE PROGRAMAS EDUCACIONAIS: a parceria entre o Governo do Maranhão e o Instituto Airton Senna no Projeto Gestão Nota 10 - Oliveira, Ildoana Paz (2013)
This paper aims to analyze the management of education in the perspective of the third sector, highlighting the mechanisms underlying the partnership between the Instituto Ayrton Senna Foundation and the Government of the State of Maranhão, in the implementation of the Program Management Note 10 by the state Department of Education, along the public schools for a period of 05 years, started in mid-2009. Because it is an object of study that depicts the partnership between public and private in management education, we outline the research process from issues that might allow grasping movement of education in our society, especially in Maranhão , locus of research, as a public policy, leading us to understand how to place the insertion of the third sector in education, from the 90s, come from a series of renovations orchestrated by multilateral organizations: the presence of the third sector in the management of education contributes to the improvement of the quality indicators in education? How did the partnership between the State Government and the Ayrton Senna Foundation? How are operationalized actions proposed by the Project Management Note 10? How is project monitoring? What quality criteria assigned in implementing the Program Management Note 10? This paper is a theoretical and methodological ruled in historical and dialectical materialism. Materialist dialectics and historical, as adopted method allows us to grasp the reality studied their movement, its transience, its totality and contradiction, contributing to the transformation of facts sociais.Para both with regard to methodological organization and the theoretical foundation, we highlight the contributions of several authors such as Marx (1983), Fernandes (1994), Gentili (1998), Gajardo (1999), Frigotto (1999), Krawczyk, Campos and Haddad (2000), Casassus (2000), Montano (2005), Lombardi, Jacomeli and Silva (2005), Peroni and Adrião (2005), Coutinho (2008), Peroni (2008), Harvey (2008), Oliveira and Rosar (2010), Ferreira (2011) and Cavalcanti (2011). The program serves 545 Management Note 10 schools, among them, 183 are from High School, 162 municipalities in Maranhão, accounting for 242,990 students and 6,983 classes. The development program will give socialization through the material support provided by the IAS in containing data as grades, attendance, attendance, dropout, distortions age / series, being filled with teachers and principals. The data are tabulated monthly on forms provided by the 9 IAS ready as a tool for monitoring indicators of school. This material is sent to the Department of Education (SEDUC) which, in turn, records the data in SIASI (Airton Senna Information System) for analysis and evaluation of the IAS. Subsequently the material returns to the team SEDUC with indications of improvements in the planning of goals for subsequent years. The Program Management Note 10 is an example of shifting the focus of the problem of educational management for actions undertaken by Third Sector institutions, with the transfer of public resources to private.